Prophetic Ethics: The Basic Value of Public Service Ethics - Briando, Bobby; Embi, Muhamad Ali (UUM Press, 2020)
Dialectics of public service in providing services to the community is always involved in social interactions that do not stop. Very complex interactions involving not only theories related to public service, but also heterogeneous and dynamic human individuals who are involved either directly or indirectly. This research aims to build the concept of prophetic ethics as the basis of the ethical values of public service. This research uses a qualitative descriptive approach in building the concept of prophetic ethics. The main bases of the theory are adopted from the spirit and the prophetic principle of profetic which is classified respectively into the four elements of the establishment, namely humanity, scholarly, pregnancy as well as humanist, emancypatorist, transcendental and Teleological. This ethical concept has an orientation on the highest human spiritual peaks, namely the divine and prophetic consciousness. With such awareness of public service not only give service to society in general, but also as a form of devotion of a servant to the creator. Prophetic ethic recognizes the existence of empirical knowledge and not empirical. From the science was then made a practical formulation in the form of “prophetic law”, which was finally called by the name “prophetic ethics”. Prophetic ethics is an endeavor that the writer undertakes in internalizing a principle and spirit that holds fast to a holistic awareness that is divine and prophetic awareness. Thus the concept of public service is not only to dethrone obligations in providing service but also as a form of devotion of a servant to its creator.